EMOTIONAL INTELLIGENCE AS A FACTOR OF PERSONAL READINESS FOR MARRIED LIFE (Psychology Travelogs, 2024)
In the context of modern societal changes that affect the structure and functions of marital relationships, individuals are required to develop a higher level of psychological maturity for successful adaptation to married life. The ability to establish emotional connections, demonstrate empathy, and constructively resolve conflicts are key characteristics that contribute to harmonious marital relationships. Emotional intelligence (EI) plays a critical role in personal readiness for marriage, as it enables individuals to understand and regulate their own emotions and those of others. Despite the growing interest in emotional intelligence in interpersonal interactions, its role in marital readiness remains underexplored. While there are individual studies on the impact of emotional competence on marital relations, a systematic approach to understanding these factors has yet to be fully developed. This article aims to examine emotional intelligence as an essential factor in personal readiness for marriage and analyze its influence on interpersonal relationships, adaptability, and harmony in marital life. The tasks of the article include analyzing the concept of EI as a psychological phenomenon, uncovering its structure and main components, and studying its influence on the development of harmonious relationships, conflict resolution, and marital adaptation.The article presents the role of emotional intelligence in preparing individuals for marriage and fostering healthy, stable marital relationships. It reviews existing literature on emotional intelligence in the context of marriage, highlighting key aspects such as emotional awareness, regulation, and empathy. High emotional intelligence contributes to better conflict resolution, emotional support, and communication within partnerships, ensuring long-term relationship stability.
Keywords: emotional intelligence; marital readiness; interpersonal relationships; conflict resolution; emotional competence